PENGARUH HUMAN RELATIONS TERHADAP KINERJA PEGAWAI DI KANTOR WILAYAH KEMENTERIAN AGAMA PROVINSI SULAWESI TENGAH - Asrifah, Asrifah (Katalogis, 2015)
This study aimed to examine the effect of independent variable human relations on employee performance. The data in this study were collected by the method of observation, interview and questionnaires. Data analysis techniques used multiple regression analysis. The population in this study is all employees in the Ministry of Religious Affairs Regional Office of Central Sulawesi Province as many as 126 people. The sampling technique used is proportional stratified random sampling, which took samples of the number of respondents as many as 96 employees. The theory used the principle of human relations from Reece, Brant and Howie, while the performance used Sumarsono theory. The results of this study simultaneously showed a positive and significant relationship between human relations and employee performance by 0.649 or 64.9% with the level of the relationship amounted to 62.1% which means included in the category of Strong influence. In the other words it can be stated that if human relations increases, the performance of employees also increased, and vice versa if human relations also decreases the performance decreases. Partially, the dominant dimension of human relations significantly affect to the performance of employees in the Ministry of Religious Affairs Office of Central Sulawesi Province is Trust (x1.5), while the lowest dimension contributes is Motivation (X1.4). Meanwhile, Self-Disclosure dimension (X1.6) provide no significant effect on the performance of employees.